Analiza bazy rynku terminowego na Giełdzie Papierów Wartościowych w Warszawie - Porcenaluk, Paweł (The Analysis of the Index Futures Basis on the Warsaw Stock Exchange, 2006)
This article analyzes the behavior of the basis over the life of an index futures contract. If futures prices do become increasingly volatile as maturity is approached, then that result has important implications for the behaviour of the basis over the life of the contract. This article shows that the volatility of changes in the basis has to decline as maturity approaches and it means that hedging in nearer contract involves less basis risk than hedging with the help of a more distant contract. What is important, basis provides information to all investors about the tendency of the futures prices on both futures and cash markets. The basis is affected by expected changes in a spot market. The results cast some light on the informational content of the basis and on the dominant role of the futures markets over cash markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 476-485